Metastatic Acinar Cell Carcinoma of the Pancreas: A Retrospective Cohort Study on Systemic Chemotherapy and Review of the Literature. Issue 3 (March 2021) - Busch, Elena; Werft, Wiebke; Bougatf, Nina; Hackert, Thilo; Jäger, Dirk; Springfeld, Christoph; Berger, Anne Katrin
Abstract : Objectives: Acinar cell carcinoma of the pancreas (pACC) forms a rare subgroup of pancreatic tumors. We report on our institutional experience with systemic first- and further-line therapy in patients with metastatic pACC and embed our findings in a review of the literature. Methods: Patients with stage IV pACC who started systemic treatment between 2008 and 2019 at our institution were identified via our institutional database. Clinical data were extracted from the patients' electronic data records. Survival times were calculated by the Kaplan-Meier method. Results: Six patients received a fluoropyrimidine- and oxaliplatin-containing first-line treatment, and 4 patients were started on gemcitabine-based protocols. Median progression-free survival was 4.8 months [95% confidence interval (CI), 3.3 to not available (n.a.)], and median overall survival was 15.3 months (95% CI, 10.1 to n.a.). Residual survival for second-line treatment was 2.1 months (95% CI, 1.3 to n.a.), although 1 patient experienced almost complete remission under targeted therapy. Conclusions: The most encouraging and deep responses result from poly-chemotherapy with leucovorin, 5-fluorouracil, irinotecan, and oxaliplatin (FOLFIRINOX), which seems to be the appropriate choice in fit patients. Gemcitabine monotherapy seems without substantial activity in pACC. Whenever possible, patients with pACC should be screened for targetable mutations.